L factor that is required for beta-galactosidase synthesis is the nusA gene product involved in transcription termination. - Greenblatt, J (1980)
The DNA-dependent in vitro synthesis of Escherichia coli beta-galactosidase requires the presence of a soluble protein referred to as L factor [Kung, H., Spears, C. & Weissbach, H. (1975) J. Biol. Chem. 250, 1556-1562]. In the present study, comparison of physical, immunological, and biological properties shows that L factor is the product of the E. coli nusA gene. The nusA gene product is known to interact with bacteriophage lambda N gene protein and to prevent premature termination of transcription from the early lambda promoters. Our results suggest that premature transcription termination in the lac operon of E. coli may also be overcome by the nusA protein.